Punitive gears in the occupations of expanded center of the city of São Paulo: experiences of control and punishment in the trajectories of life and struggle for housing - Ananda Endo (Geografares, 2022)
This article, a partial result of a master's research in progress with the support of the São Paulo Research Foundation (FAPESP), intends to contribute with notes about the penal tactics taken as analyzers of the power relations at stake in housing occupations of the expanded center of the city of São Paulo. The material of analysis are trajectories and experiences of residents marked by the relationship with the punitive devices of the State (with emphasis on the prison), gathered through ethnographic fieldwork, in comparison with other sources (judicial proceedings, media, interview).
Keywords: penal tactics; occupations; prison